KNOWLEDGE ATTITUDE AND PRACTICES ABOUT ENDOSCOPY PROCEDURES AMONG NURSES OF NISHTAR HOSPITAL MULTAN - PARVEEN , K; PARVEEN, M; PARVEEN, R (Biological and Clinical Sciences Research Journal, 2023)
This study explores nurses' knowledge, attitudes, and practices in gastrointestinal endoscopy procedures, focusing on nurses from Nishtar Hospital Multan. It explores their understanding and practical application of endoscopy protocols and their pivotal role in patient care and procedure management. In a cross-sectional study conducted at Nishtar Hospital Multan, data was collected from 150 nurses using a Likert scale questionnaire. The research considered participants willing to participate and provided informed consent. Data analysis was carried out using SPSS software. The demographic profile of the nurses revealed a predominantly female workforce (56%). Age-wise, the majority were under 45 years old (38%). About 80% held a diploma degree, indicating specialized training. A significant portion had eight years of work experience (82%). In terms of endoscopy experience, 72.7% had less than 10 years. Most received training (82%) and were vaccinated against Hepatitis B (82%). In terms of attitudes and practices, the nurses displayed a high level of agreement with key hygiene and infection control practices, such as handwashing, with 100% agreement in some cases. They also recognized the importance of infection prevention through measures like masks, gowns, and gloves . Furthermore, they acknowledged the significance of patient comfort and the need to provide information to patients during endoscopy. The study reveals that while nurses possess strong knowledge and positive attitudes toward endoscopy procedures, ongoing training and continuous assessment are necessary to ensure optimal practices. Nurses play a crucial role in patient care and procedural success, prioritizing their comprehensive education and training. Further research and periodic evaluation can drive improvements in their work's theoretical and practical aspects, ultimately enhancing patient outcomes and safety in endoscopy units.